2013
DOI: 10.1128/iai.00942-12
|View full text |Cite
|
Sign up to set email alerts
|

The Haemophilus influenzae Sap Transporter Mediates Bacterium-Epithelial Cell Homeostasis

Abstract: Nontypeable Haemophilus influenzae (NTHI) is a commensal inhabitant of the human nasopharynx and a causative agent of otitis media and other diseases of the upper and lower human airway. During colonization within the host, NTHI must acquire essential nutrients and evade immune attack. We previously demonstrated that the NTHI Sap transporter, an inner membrane protein complex, mediates resistance to antimicrobial peptides and is required for heme homeostasis. We hypothesized that Sap transporter functions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 87 publications
(118 reference statements)
5
48
0
Order By: Relevance
“…The size of each circle is scaled to the number of nodes contained within. The top 10 significantly overrepresented nodes within each ontological category are listed on the figure, whereas all nodes are listed in supplemental Tables S8 -S13. ent with previous reports (22), in the absence of CK-636 viable internalized NTHI were not observed in NHBE cells following 24 and 48 h of infection. When Arp2/3 function was inhibited, we observed gross morphological changes in actin structure and an increase in the number of extracellular bacteria indicating that bacterial uptake was reduced (Fig.…”
Section: Fig 2 Graphical Summary Of Overrepresented Proteins Categosupporting
confidence: 76%
“…The size of each circle is scaled to the number of nodes contained within. The top 10 significantly overrepresented nodes within each ontological category are listed on the figure, whereas all nodes are listed in supplemental Tables S8 -S13. ent with previous reports (22), in the absence of CK-636 viable internalized NTHI were not observed in NHBE cells following 24 and 48 h of infection. When Arp2/3 function was inhibited, we observed gross morphological changes in actin structure and an increase in the number of extracellular bacteria indicating that bacterial uptake was reduced (Fig.…”
Section: Fig 2 Graphical Summary Of Overrepresented Proteins Categosupporting
confidence: 76%
“…The pathogen also utilizes urease, found to be more prevalent in disease-causing isolates than commensals, to survive in acid environments [43,44]. Other systems involved in sensing the microenvironment within the host include the multifunctional Sap-transporter, possibly via detection of host molecules as well as heme accessibility [45,46]. As alluded to by its name, Haemophilus lacks the ability to synthesize heme that is essential for its survival.…”
Section: Niche Adaptability and Nutrient Acquisitionmentioning
confidence: 98%
“…We showed that NTHiderived outer membrane vesicles (OMVs) carried functional b-lactamase that protected GAS from amoxicillin-mediated killing. Interestingly, NTHi OMV shedding is seen in several infection models, suggesting that they may play important roles during pathogenesis [22,45].…”
Section: Polymicrobial Infectionsmentioning
confidence: 99%
“…In addition, NTHiinduced OM middle ear effusions are frequently sanguineous, likely a result of these hallmarks of middle ear inflammation (92; B. Szelestey and K. Mason, unpublished observations). NTHi invasion of host epithelial cells may also provide a mechanism of nutrient acquisition when bacteria are exposed to nutrient-limiting conditions in the host (92). NTHi infection of the middle ear coincides with an influx of polymorphonuclear leukocytes (PMNs).…”
Section: Discussionmentioning
confidence: 99%